Dysfunctional mitochondrial Ca2+ handling in mutant SOD1 mouse models of fALS: integration of findings from motor neuron somata and motor terminals - Barrett, Ellen F.; Barrett, John N.; David, Gavriel (Frontiers in Cellular Neuroscience, 2014)
Abundant evidence indicates that mitochondrial dysfunction and Ca2+ dysregulation contribute to the muscle denervation and motor neuron death that occur in mouse models of familial amyotrophic lateral sclerosis (fALS). This perspective considers measurements of mitochondrial function and Ca2+ handling made in both motor neuron somata and motor nerve terminals of SOD1-G93A mice at different disease stages. These complementary studies are integrated into a model of how mitochondrial dysfunction disrupts handling of stimulation-induced Ca2+ loads in presymptomatic and end-stages of this disease. Also considered are possible mechanisms underlying the findings that some treatments that preserve motor neuron somata fail to postpone degeneration of motor axons and terminals.